Development of an ethnoscience-based vocational learning model for solar-wind hybrid energy systems in small-scale fishing vessel applications - Zakiah, Diah; Jaya, Indra; Rahmat, Ayi; Priandana, Karlisa; Iskandar, Budhi Hascaryo (Indonesian Journal of Science and Mathematics Education, 2025)
Coastal communities increasingly require accessible renewable-energy education, yet conventional vocational programs rarely integrate local maritime knowledge or hands-on, culturally relevant practices. This study aims to develop and evaluate an ethnoscience-based vocational learning model that uses a simple wave-energy converter as a contextual tool. A qualitatively driven mixed-methods design was employed involving fishers, vocational students, teachers, and local stakeholders through interviews, focus group discussions, observations, and classroom implementations. Findings show that the model effectively bridges indigenous maritime knowledge with renewable-energy engineering concepts, producing pedagogically meaningful outcomes: a 21% increase in students’ conceptual understanding and a 139–270% improvement in psychomotor skills related to device design, measurement, and troubleshooting. Teachers reported enhanced capacity in contextual and multimodal instructional design, while community members recognized the model’s relevance to local energy needs. The study demonstrates that culturally grounded, low-cost engineering activities can strengthen STEM learning in resource-constrained coastal settings. These results have implications for integrating ethnoscience into vocational curricula, supporting equitable education, preserving local knowledge, and accelerating the adoption of community-based renewable technologies. This model offers a measurable pathway for policy development in vocational education, energy transition, and fisheries.